Policing Under Colonial Shadows: The Profiling of Afghan Refugees - Noor Fatima (Dialogue Social Science Review (DSSR), 2025)
This research critically investigates the enduring legacy of colonial rule principles on policing and profiling Afghan refugees in Quetta, Pakistan. At the nexus of Postcolonial Theory, Structural Violence Theory, and Institutional Theory, this research demonstrates how the long-term principles of colonial power continue to shape contemporary institutional conduct and everyday lives of displaced Afghan communities. Despite Pakistan's long-standing history as a haven for Afghan refugees since the Soviet invasion, the absence of a specific national refugee law, along with continued reliance on colonial-era statutes like the Police Act of 1861 and the Foreigners Act of 1946, creates a culture of legal ambiguity and discretionary enforcement. Adopting an interpretivist, qualitative methodology inspired by the Research Onion model, the research employs in-depth, semi-structured interviews with Afghan refugees, local police officials, and governance representatives. NVivo-assisted thematic analysis demonstrates that structural violence is made normal through everyday policing encounters that systematically reproduce ethnic profiling, arbitrary surveillance, and coercive monitoring. Particular focus is given to the Hazara subcommunity, whose overlapping vulnerabilities reveal the compounded effects of sectarian identity and refugee status. Findings point to institutional stagnation and policy loopholes reproducing discriminatory principles from the colonial state, despite professed commitments to community-based policing and protection strategies. The author asserts that decolonizing governance in Pakistan necessitates the elimination of legal artifacts, the adoption of rights-based policing practices, and the establishment of effective accountability mechanisms. In doing so, it makes an original contribution to the scholarship on postcolonial policing, forced migration, and structural violence in the South Asian context.